Analisis Vegetasi Di Sekitar Area Bunker Kawasan Taman Nasional Gunung Merapi - Alima, Nadia; Nugroho, Edo Cahyo; Rizki, Elsa Wahyu; Intan, Afifah; Ifani, Elisa Feby (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2020)
Diversity studies and important value indices have been carried out on forest vegetation in the Mount Merapi National Park area using the Quadrat Sampling Technique method. The specified plot size is 6x6m2. There are 2 plots used. Forest diversity in the Mount Merapi National Park is determined using the Shannon diversity index formula. The results show that the species diversity index of moss-lichen habitus and stand habitus is 0, which means that these two habitus have no diversity. Both of these habitus have only one species that grows in the study area, while the species diversity index in shrub habitats was 0.426673041. Habitus which has the highest species diversity index is herbal habitus which is 0.734014356. In this study found as many as 12 species consisting of one species of moss-lichen habitus, 7 species of herbaceous habitus, 3 species of bush, and one stand habitus species. The highest important index value for moss - lichen habitus is Diphasiastrum sp. (300%), Viburnum sp. for herbal habitus (100.96%), Carex sp. for shrub habitus (132.63%), and Acacia sp. for stand habitus (300%).